2021
DOI: 10.3847/2041-8213/abe7dd
|View full text |Cite
|
Sign up to set email alerts
|

The Core Mass Function in the Orion Nebula Cluster Region: What Determines the Final Stellar Masses?

Abstract: Applying dendrogram analysis to the CARMA-NRO C18O (J = 1–0) data having an angular resolution of ∼8″, we identified 692 dense cores in the Orion Nebula Cluster region. Using this core sample, we compare the core and initial stellar mass functions in the same area to quantify the step from cores to stars. About 22% of the identified cores are gravitationally bound. The derived core mass function (CMF) for starless cores has a slope similar to Salpeter’s stellar initial mass function (IMF) for the mass range ab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 52 publications
3
10
0
Order By: Relevance
“…This picture is in agreement with competitive accretion scenarios (Bonnell et al 2001(Bonnell et al , 2004, global hierarchical collapse (Vázquez-Semadeni et al 2019), and the inertial flow model (Padoan et al 2020;Pelkonen et al 2021). Recently, Takemura et al (2021) pointed out that the cores need to accumulate gas from their surroundings to reproduce the stellar IMF from the present core mass function in the Orion Nebula Cluster region. In a different IRDC of the ASHES survey, Contreras et al (2018) estimate a core infall rate of 2 × 10 −3 M yr −1 .…”
Section: Evolutionary Stagessupporting
confidence: 81%
“…This picture is in agreement with competitive accretion scenarios (Bonnell et al 2001(Bonnell et al , 2004, global hierarchical collapse (Vázquez-Semadeni et al 2019), and the inertial flow model (Padoan et al 2020;Pelkonen et al 2021). Recently, Takemura et al (2021) pointed out that the cores need to accumulate gas from their surroundings to reproduce the stellar IMF from the present core mass function in the Orion Nebula Cluster region. In a different IRDC of the ASHES survey, Contreras et al (2018) estimate a core infall rate of 2 × 10 −3 M yr −1 .…”
Section: Evolutionary Stagessupporting
confidence: 81%
“…This result has been consistently found through (sub)millimeter continuum observations with ground-based single-dish telescopes (e.g., Motte et al 1998;Motte & André 2001;Stanke et al 2006;Enoch et al 2008) and interferometers (e.g., Testi & Sargent 1998). It has been confirmed with deep, far-infrared to submillimeter images obtained by the Herschel space observatory (e.g., Könyves et al 2015;Benedettini et al 2018;Massi et al 2019;Ladjelate et al 2020) and a handful of near-infrared extinction maps and molecular line integrated images (Alves et al 2007;Onishi et al 2001;Takemura et al 2021). The astonishing similarity between the IMF and the observed CMFs, all of which are consistent with each other, suggests that the IMF may inherit its shape from the CMF (e.g., Motte et al 1998;André et al 2014).…”
Section: Introductionmentioning
confidence: 62%
“…This area was recently observed by CRAMA-NRO (Kong et al 2018). Using CARMA-NRO C 18 O (J = 1 − 0) data, Takemura et al (2021) identified approximately 200 dense cores in the filamentary region of ONC (∼1 pc −3 area), which gives a number density of n c ∼ 200 pc −3 . If we adopt r c = 0.05 pc and 〈v〉 = 1 km s −1 as representative values, we can derive the collision time τ coll ∼ 0.3 Myr using Equation (3).…”
Section: Introductionmentioning
confidence: 58%
“…If we adopt r c = 0.05 pc and 〈v〉 = 1 km s −1 as representative values, we can derive the collision time τ coll ∼ 0.3 Myr using Equation (3). Takemura et al (2021) derived the core lifetime in Orion A of ∼ 5 t ff for starless cores with densities of ρ 0 ∼ 10 4 -10 5 cm −3 , where…”
Section: Introductionmentioning
confidence: 99%